2020
DOI: 10.1021/acs.iecr.0c04043
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Predict Thermodynamic Data from Spectroscopic Analysis

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…UNIFAC (Do) though. In a more general case of alkane–ketone VLE predictions, an accurate alternative approach from MIR was demonstrated by ten Kate et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UNIFAC (Do) though. In a more general case of alkane–ketone VLE predictions, an accurate alternative approach from MIR was demonstrated by ten Kate et al…”
Section: Resultsmentioning
confidence: 99%
“…Further developments in this direction such as feeding UNIFAC with group contribution terms based on COSMO-RS predictions might offer an interesting approach for the characterization of unparametrized groups. An approach proposed by ten Kate et al has demonstrated the feasibility of extracting nonideal behavior information from spectroscopic information alone. These authors showed, as an example, that liquid phase activity coefficients and VLE for binary mixtures of compounds for different molecular family combinations (e.g., alkanes–ketones, alcohols–ketones, and alkanes–alcohols) could be predicted accurately based on measured mid-infrared (MIR) spectra for these mixtures and a data-driven partial least-squares (PLS) model connecting the excess absorbance from the MIR spectrum to the Gibss excess energy ( g E ) of the mixture for that molecular family combination calibrated for only a limited number of different mixtures from the same molecular family combination .…”
Section: Introductionmentioning
confidence: 99%
“…21 Very recently, it has been used to correlate activity coefficients of binary liquid mixtures. 22 It is applicable to molecular spectroscopy methods such as IR, Raman, UV− vis, and so on. Particularly for IR, this method is widely suitable, regardless of the near-infrared, mid-infrared, or farinfrared range.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, in addition to the resolution improvement feature, excess spectroscopy can also be used to judge the nonideality of mixtures , and to determine the selectivity of molecular interactions . Very recently, it has been used to correlate activity coefficients of binary liquid mixtures . It is applicable to molecular spectroscopy methods such as IR, Raman, UV–vis, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation